Fashion and algorithms: the “Stich Fix” platform and personalization in fashion (Revista de Ensino em Artes, Moda e Design, 2024)
Digital platforms ultimately cross many activities in contemporary society; as a result, these activities are transformed by adopting the operating logic of these platforms. As a cultural, social, and economic manifestation, fashion does not escape this process. This paper aims to analyze the “Stitch Fix” platform from datafication and algorithms, infrastructure, business model, and governance (D’Andréa, 2020). It is concluded that Stitch Fix is part of the network created by the Big Five, with a business model that integrates four main stakeholders (consumers, companies, brands, and stylists) and sells combinations of clothes from boxes and the respective products. Fashion makes it up. The platform’s governance reveals privacy control relationships linked to North American legislation, with data being shared with external platforms. The datafication and algorithms promote a data extraction and recommendation process that culminates in a fashion personalization process based on combining pieces.
Keywords: personalized fashion; platformization; digital economy